Multi-Unit Open Ascending Price Efficient Auction - Sergei Izmalkov (Fondazione Eni Enrico Mattei (FEEM), 2004)
This paper presents an open ascending price mechanism that allocates efficiently M units of the same good among N bidders with interdependent values The mechanism consists of a number of sequential English auctions with reentry and has the following attributes. In each of the individual auctions all the bidders compete simultaneously in the open ascending price format. The most distinctive feature of the mechanism is that winners are determined first, and then additional auxillary auctions are conducted to determine prices. The total number of auctions depends only on the number of goods to be allocated and not on the number of bidders.
Keywords: C72; D44; 330; Multiple units; Interdependent values; Sequential auctions; Ascending price auction; Auktionstheorie; Marktmechanismus; Allokationseffizienz